Estabilização de um solo argiloso com cal de carbureto - Borges, Humberto Félix (1979)
The purpose of this research work was to verify the behavior of the waste lime in stabilization of a kaolinitic clay. Parallel to this, a comparative study was done between the effects of the waste lime and the effects of a calcitic hidrated lime on this soil. The steps of this research work consisted of: analysis of the waste lime, of the calcitic lime, and analysis of the soil; the effects of the waste lime and the effects of calcitic lime, in varied proportions, in stabilization of this soil; conclusions.